Area Assessment of English in the Application of Edupreneurship in Convention and Event Business Management in a Public Tourism Polytechnic - Suparto, Windy Puspitasari; Lao, Yandres A. Dj.; Salim, Muhammad Arfin Muhammad (Journal of Language Learning and Assessment, 2023)
Purpose The purpose of this study was to identify, describe, and analyze the application of edupreneurship in convention and event business management for English classes at the Makassar State Tourism Polytechnic Methodology The qualitative descriptive method was used by researchers in this study. What is meant by "qualitative descriptive research" is survey research that determines and explains the use of the strategy for implementing the Makassar State Tourism Polytechnic. Results/Findings In general, it can be said that the results of research related to the implementation of edupreunership through teaching factories show the commitment of vocational institutions or tertiary institutions to edupreneurship learning. This is evidenced by the empowerment of entrepreneurship aimed at all levels, this fact proves that entrepreneurship subjects have strategic meaning for students and institutions. Implications The conclusion highlights that while schools aim to align with edupreneurship through teaching factories, they face challenges in synchronizing with business and industry practices. These hurdles include deficiencies in work culture adherence, teaching staff's unfamiliarity with industry standards, unmet infrastructure benchmarks, universities' insufficient collaboration with industry entities, and regulatory constraints imposing the use of state assets for revenue generation